Breast Suspicious Microcalcifications on Contrast-Enhanced Mammograms: Practice and Reflection - Zhao X (International Journal of General Medicine)
Xue Zhao Department of Radiology, Huangpu Branch, Shanghai Ninth People’s Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, 200011, People’s Republic of ChinaCorrespondence: Xue Zhao, Department of Radiology, Huangpu Branch, Shanghai Ninth People’s Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, 200011, People’s Republic of China, Tel +86 17612189294, Email zhaoxue@alumni.sjtu.edu.cnPurpose: To evaluate the use of contrast enhanced mammography (CEM) in suspicious microcalcifications and to discuss strategies to cope with its diagnostic limitations.Methods: We retrospectively evaluated patients with suspicious calcifications who underwent CEM at our institution. We collected and analyzed morphological findings, enhancement patterns and pathological findings of suspicious microcalcifications on CEM. A small proportion of these cases underwent dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). The enhancement patterns of CEM in this study were classified into three categories: enhancement, no enhancement, and indeterminate. CEM imaging was independently analyzed by two breast imaging specialists.Results: A total of 44 patients with 46 lesions were collected from January 2022 to July 2024. Overall, 20 cases (43.5%) microcalcifications showed enhancement on CEM; 23 (50.0%) showed no enhancement; and 3 (6.5%) were indeterminate. Of the 20 enhancement cases, mass enhancement was seen in 9 (45%), and non-mass enhancement (NME) in 11 (55%). DCE-MRI was performed in 13 cases. One case of invasive ductal carcinoma (IDC) showed enhancement on MRI but was indeterminate on CEM due to the masking effect of background parenchymal enhancement (BPE), and one case of ductal carcinoma in situ (DCIS) lacked enhancement on CEM but had significant enhancement on MRI.Conclusion: CEM provides additional information on the enhancement associated with breast suspicious microcalcifications. It is not perfect for diagnosis and strategies are needed to cope with its limitations.Keywords: microcalcifications, contrast-enhanced, mammography, diagnostic imaging, breast